Identification of Shewanella putrefaciens as a novel pathogen of the largemouth bass (Micropterus salmoides) and histopathological analysis of diseased fish - Jiang, Xinyu; Wang, Xiaoyu; Li, Lei; Niu, Chen; Pei, Chao; Zhu, Lei; Kong, Xianghui (Frontiers in Cellular and Infection Microbiology, 2022)
The largemouth bass (Micropterus salmoides) is an economically important aquaculture species in China, and its production has increased rapidly in recent years. Although Shewanella putrefaciens is known to infect several fish species, its role in infecting M. salmoides is relatively unknown. Here, we isolated a gram-negative bacterial strain (termed XX2021) from farmed largemouth bass. Based on the results of 16S rRNA sequencing and phylogenetic analyses, the isolate was identified as S. putrefaciens. The virulence of XX2021 was dependent on water temperature, such that the LD50 values were 4.21×104, 7.26×105, and 2.47×106 CFU/g fish weight at 10 °C, 18 °C, and 25 °C, respectively. Four virulent genes—including dksA, hem, lonR, and fur—were screened through a PCR assay. The results of an antibiotic resistance test showed that XX2021 was sensitive to kanamycin, cefotaxime, doxycycline, sulfamethoxazole, florfenicol, tetracycline, and gentamicin; showed intermediate susceptibility to streptomycin, ampicillin, and norfloxacin; and was resistant to nalidixic acid and penicillin. XX2021-infected fish showed clinical symptoms typical of S. putrefaciens infection. In addition, we re-isolated XX2021 from infected fish and confirmed its identity using 16S rRNA sequencing. Histopathological changes were observed in the intestine, head kidney, spleen, and liver of diseased fish. This study presents the first report of the pathogenic effects of S. putrefaciens in farmed largemouth bass. Our findings may help develop effective disease control strategies for aquaculture fish and prevent disease outbreaks under low water temperatures.